Soil Saprobic Fungi Differ in Their Response to Gradually and Abruptly Delivered Copper - Golubeva, Polina; Ryo, Masahiro; Muller, Ludo A. H.; Ballhausen, Max-Bernhard; Lehmann, Anika; Sosa-Hernández, Moisés A.; Rillig, Matthias C. (Frontiers in Microbiology, 2020)
The overwhelming majority of studies examining environmental change deliver treatments abruptly, although, in fact, many important changes are gradual. One example of a gradually increasing environmental stressor is heavy metal contamination. Essential heavy metals, such as copper, play an important role within cells of living organisms but are toxic at higher concentrations. In our study, we focus on the effects of copper pollution on filamentous soil fungi, key players in terrestrial ecosystem functioning. We hypothesize that fungi exposed to gradually increasing copper concentrations have higher chances for physiological acclimation and will maintain biomass production and accumulate less copper, compared to fungi abruptly exposed to the highest copper concentration. To test this hypothesis, we conducted an experiment with seventeen fungal isolates exposed to gradual and abrupt copper addition. Contrary to our hypothesis, we find diverse idiosyncratic responses, such that for many fungi gradually increasing copper concentrations have more severe effects (stronger growth inhibition and higher copper accumulation) than an abrupt increase. While a number of environmental change studies have accumulated evidence based on the magnitude of changes, the results of our study imply that the rate of changes can be an important factor to consider in future studies in ecology, environmental science, and environmental management.